Role Conflict, Role Ambiguity and Job Satisfaction of County Extension Agents in the Georgia Cooperative Extension Service - Bille Chambers; A.B. Moore; Douglas Bachtel (Adult Education Research Conference, 1998)
Organizational, job related and personal correlates of role conflict, role ambiguity and job satisfaction were examined for County Extension Agents in Georgia. The findings are discussed in terms of their implications for in-service training program.